(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
This article describes the methods of treatment of odontogenic cysts of the jaw bones in children and the surgical rehabilitation of patients with this pathology. Literature data on various methods of surgical treatment of odontogenic cysts of the jaw bones in children are summarized. The prospects of recognition of odontogenic cysts in computed tomography are noted, the decisive preference in making a diagnosis is given to a mandatory pathohistological examination.